A Python toolkit for visualizing greenhouse gas emissions at sub-county scales. (September 2016) - Wohlstadter, Michael; Shoaib, Lubna; Posey, John; Welsh, Jason; Fishman, Jack
Abstract: This short communication describes a package written in the Python language that facilitates analysis and visualization of transportation-related greenhouse gas emissions at sub-county scales. Known as the Small Area Greenhouse Gas Estimation Tool (SAGGET), the toolkit uses outputs from the Motor Vehicle Emission Simulator (MOVES) emission model to create emissions estimates and projections for user-defined geographies. The Python scripts issue calls to third party geoprocessing libraries; separate versions of the toolkit are available for use in conjunction with the ArcGIS library produced by ESRI, and for the open-source SpatiaLite extension to the SQLite database engine. We demonstrate the capacity of the toolkit by presenting small-area emissions estimates for the St. Louis region as a whole, and for a specific transportation corridor. The package is freely available from the East-West Gateway Council of Governments. Highlights: Software tools provide method for analyzing and visualizing transportation-related greenhouse gas emissions. The software, written in the Python language, allows users to define geographic scale for analysis. Potential applications involve corridor planning and remote sensing calibration. Toolkit processes outputs from the U.S. Environmental Protection Agency's MOVES emissions model.